2014
DOI: 10.1074/jbc.m114.596148
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assembly of Catalase

Abstract: Background: Catalase is a heme protein of intricate structural organization, and its assembly is not understood.Results: Apocatalase in E. faecalis was found synthesized independent of heme, and procedures for its purification and hemylation were established.Conclusion: Catalase can be assembled in vitro.Significance: The reported findings open up for new in vitro experimental approaches to study heme protein biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
(40 reference statements)
3
12
0
Order By: Relevance
“…One recent in vitro study using Enterococcus faecalis catalase demonstrated the importance of heme insertion in formation of tetrameric active catalase(14). To understand heme maturation of catalase in mammalian cells, we utilized our previous finding of NO-mediated inhibition of heme maturation into catalase to identify factors regulating its heme incorporation and therefore tetramerization to make the active enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent in vitro study using Enterococcus faecalis catalase demonstrated the importance of heme insertion in formation of tetrameric active catalase(14). To understand heme maturation of catalase in mammalian cells, we utilized our previous finding of NO-mediated inhibition of heme maturation into catalase to identify factors regulating its heme incorporation and therefore tetramerization to make the active enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In rat liver apo-catalase is present in 3 fold excess (1.6% compared to 0.5%) of holo-monomeric catalase (13). Lack of heme can increase the pool of apo-catalase and may promote its turnover (14,15). Exposure to oxidative stress can inactivate catalase (16-19), but whether this affects its structure is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Being a heme-catalase, KatB (EC 1.11.1.6) depends on its co-factor, heme, for the enzymatic activity of reducing H 2 O 2 to H 2 O [41]. However, the production of monomeric apo-catalase does not rely on heme [42]. Given that iron availability has no impact on catalase expression in V. cholerae [43], we hypothesized that iron content would affect catalase activity at the post-translational level, which could be partially compensated by CBS-derived H 2 S. To test this hypothesis, we examined the impact of cbs expression on KatB activity in V. cholerae cells under iron-deficient (achieved by supplementation of iron chelator 2,2'-bipyridine) or iron-enriched (achieved by supplementation of FeCl 3 ) conditions.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…The rate of hydrogen peroxide decomposition at 37 °C was recorded as the decrease in absorption at 240 nm, and activity was calculated based on the initial rate (up to 20 s). One unit was defined as the decomposition of 1 μmol of hydrogen peroxide per minute …”
Section: Methodsmentioning
confidence: 99%